2022
DOI: 10.1002/adma.202206569
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Agglomeration of Single‐Atom Platinum in Photocatalysis

Abstract: With recent advances in the field of single‐atoms (SAs) used in photocatalysis, an unprecedented performance of atomically dispersed co‐catalysts has been achieved. However, the stability and agglomeration of SA co‐catalysts on the semiconductor surface may represent a critical issue in potential applications. Here, the photoinduced destabilization of Pt SAs on the benchmark photocatalyst, TiO2, is described. In aqueous solutions within illumination timescales ranging from few minutes to several hours, light‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 86 publications
4
46
0
Order By: Relevance
“…Moreover, for the sputtered layers deposited in 0.005 mM and 2 mM H 2 PtCl 6 solution, the corresponding density of SAs, rafts, and agglomerates after 3 h of illumination by simulated AM 1.5, as determined by segmentation of HAADF-STEM images, is shown in Table S1. In line with our previous findings, some light-induced agglomeration of Pt SAs to ensembles (dimers, multimers) and larger agglomerate takes place, as outlined in Figure S7. Although not all SAs are stable, the major part of SAs is still present after AM1.5 illumination for 3 h. This holds particularly well for the low loading (which is good enough for not limiting the H 2 evolution).…”
supporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, for the sputtered layers deposited in 0.005 mM and 2 mM H 2 PtCl 6 solution, the corresponding density of SAs, rafts, and agglomerates after 3 h of illumination by simulated AM 1.5, as determined by segmentation of HAADF-STEM images, is shown in Table S1. In line with our previous findings, some light-induced agglomeration of Pt SAs to ensembles (dimers, multimers) and larger agglomerate takes place, as outlined in Figure S7. Although not all SAs are stable, the major part of SAs is still present after AM1.5 illumination for 3 h. This holds particularly well for the low loading (which is good enough for not limiting the H 2 evolution).…”
supporting
confidence: 92%
“…4,5,7,28,36−38 Although we cannot solve this intriguing challenge here, the observed increase in H 2 evolution for low LED powers over time (Figure S6a) in combination with raft formation may suggest that slight agglomeration of SAs to multimers might be beneficial to maximize the H 2 evolution rate. In line with previous work, 28,38 it is clear, however, that light-formed nanoparticles (i.e., 3D assemblies) do not contribute to the photocatalytic activity (see Figure S8). Using the SA surface density data from HAADF-STEM and the H 2 evolution at saturation (0.17 mL H 2 per hour at 100 mW cm −2 for the 0.005 mM case, and 0.90 mL H 2 per hour at 400 mW cm −2 for the 0.05 mM and 2 mM cases), one may estimate the turnover frequency (TOF) at H 2 evolution sites as described in the Supporting Information.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…[9] Therefore, in the actual application environment and catalytic reaction conditions, especially at high temperature or in a reducing atmosphere, the single atomic metal active sites are extremely prone to agglomeration and coupling to form large atomic clusters (even nanoparticles), resulting in the degradation of catalyst performance or even complete inactivation. [10] Recently, however, scientists have found that fully exposed cluster catalysts with low coordination metal bonds (the coordination number of the metal bond is ≈4.4) [11] and local single-atomic agglomeration [12] show more satisfactory performances in specific complex catalytic systems. These works provide a basic understanding of the dynamic stability of SACs under working conditions and call for a reassessment of the reported stability of SACs by considering realistic reaction conditions.Admittedly, it is quite necessary to reevaluate the realistic catalytic stability and dynamic catalysis mechanism of SACs; nevertheless, we hold the opinion that it is more important to design fundamentally a kind of efficient SACs with high activity and high stability at the same time (such as the "moving but not aggregating" design philosophy for metal active sites).…”
mentioning
confidence: 99%